Non Contact Tonometry: a Fluid Structure Interaction study - Redaelli, Elena; Fantaci, Benedetta; Grasa, Jorge; Luraghi, Giulia; Rodríguez Matas, José Félix (Jornada de Jóvenes Investigadores del I3A, 2021)
Non Contact Tonometry is a clinical tool that records the displacement of the corneal surface caused by the application of an airflow. The measurements are not true representatives of corneal properties, but they are related. The proposed analysis simulates the test on an eye model to isolate the mechanical properties and establish clinical decisions.